2018
DOI: 10.1080/15384047.2017.1416938
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index in HER2-negative metastatic breast cancer treated with first-line paclitaxel and bevacizumab

Abstract: The evidence emerged from the TOURANDOT trial encourages evaluating the role of anthropometric determinants on treatment outcomes in HER2-negative metastatic breast cancer patients treated with bevacizumab-including regimens. We thus analyzed data from a subgroup of these patients from a larger cohort previously assessed for treatment outcomes. Patients were included in the present analysis if body mass index values had been recorded at baseline. Clinical benefit rates, progression free survival and overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…Recently, Pizzuti et al. analysed data of 196 women with HER2-negative metastatic BC, treated with paclitaxel and bevacizumab and showed that BMI had no impact on survival particularly in the luminal subgroup [ 20 ]. In contrast to our report, these studies did however not distinguish underweight from normal weight patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Pizzuti et al. analysed data of 196 women with HER2-negative metastatic BC, treated with paclitaxel and bevacizumab and showed that BMI had no impact on survival particularly in the luminal subgroup [ 20 ]. In contrast to our report, these studies did however not distinguish underweight from normal weight patients.…”
Section: Discussionmentioning
confidence: 99%
“…Variables of interest were: BMI at MBC diagnosis, classified as 4 classes (underweight, normal weight, overweight and obesity); age at diagnosis of MBC (<or ≥65 years); performance status (PS) (PS: 0, 1, 2–4); time to MBC, defined as the time from diagnosis of the primary cancer and diagnosis of MBC (<6 [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ], 24 months); metastatic sites (bone only, bone and non-visceral metastases [skin, lymph nodes …], visceral metastases [liver, brain metastases] and others); number of metastatic sites ( 3, ≥3); MBC subtypes (HR+/HER2-, HER2+ and HR-/HER2-); symptom-versus screening-based diagnosis of MBC (defined as MBC diagnosed on symptoms versus MBC discovered based on the results of a blood or imaging test). All significant factors at 15% level in univariable analysis were included in multivariable analyses.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, there is current interest in exploring the "obesity paradox" in advanced cancers 22,23 , where elevated BMI is associated with improved survival compared to normal BMI 24,25 . Where the BMI-survival relationship has been explored in advanced BC (ABC), the sample has generally been small (i.e., n < 800) and observational [26][27][28][29][30][31][32][33][34] . Further to this, most studies have been nonspecific regarding early versus ABC, ABC subtypes (e.g., HER2 positive disease), and/or treatments used [26][27][28][29][30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…Body mass index (BMI), which can be simply calculated from weight and height, has been widely used to estimate the amount of adipose tissue and many previous studies demonstrated worse prognosis for patients with high BMI in various kinds of malignancies, including colorectal cancer, breast cancer, pancreatic cancer, and hepatocellular carcinoma . However, other studies showed inconsistent results for the association between obesity and clinical outcomes . Moreover, for lung cancer and renal cell carcinoma, obesity even showed a beneficial effect on prognosis .…”
Section: Introductionmentioning
confidence: 99%